Florida Tax Exemption for Selected Farm Equipment - Edward A. Evans (EDIS)
FE715, a 3-page fact sheet by Edward A. Evans, is part of the Tax Exemption for Agricultural Producers series. It describes the Power Farm Equipment Exemption Law, what farm equipment is included, and the procedure for obtaining the tax exemption. Includes references and a sample exemption certificate. Published by the UF Department of Food and Resource Economics, August 2008.